Unraveling investment herds: Bandarmology and millennial investors in Indonesia - Wijaya, Lientang; Windhyastiti, Irany; Khouroh, Umu; Hidayatullah, Syarif (Manajemen dan Bisnis, 2024)
This study aims to investigate the impact of the concept of “bandarmology” or herd behavior (HB) on the investment decisions of millennial stock investors in Indonesia who are influenced by influencer Anton Swandana. The research adopts a quantitative approach with an ex post facto method and uses the Partial Least Square (PLS) analysis technique to test the hypothesis. Data was collected through a questionnaire distributed via Google Form to 100 respondents selected by the quota sampling technique. The results indicate that source credibility, herd behavior, risk perception, and emotional response have a significant effect on investment behavior intention. This research contributes to the field of stock investment in Indonesia by providing a deeper understanding of the behavior of millennial stock investors and the factors that influence their investment decisions.